1861. National Healthcare Safety Network's Electronic Antimicrobial Use and Resistance Surveillance: First Cohort of Hospital Reporters, 2011–2017. (26th November 2018) - Wu, Hsiu; Webb, Amy; O'Leary, Erin; Weiner, Lindsey; Neuhauser, Melinda; Van Santen, Katharina; Zhou, Liang; Edwards, Jonathan R; Pollock, Daniel
Abstract: Background: The Centers for Disease Control and Prevention's (CDC's) National Healthcare Safety Network (NHSN) Antimicrobial Use and Resistance (AUR) Module is used to monitor antimicrobial use and AR threats. Hospital participation in the module is voluntary. For hospitals to participate, data submission to the AU or AR reporting option(s) must be completed using standard electronic messages. To better understand how the mix of voluntary participation and electronic reporting requirements affects hospital uptake of the AUR Module, we characterized the first hospital cohorts of AU and AR data submitters. Methods: We compared the first hospitals that submitted data to the NHSN's AU and AR options with hospitals that reported to NHSN's healthcare-associated infection (HAI) Modules but not the AUR Module from 2011 through 2017. Early AU and AR adopters are hospitals that reported to NHSN's AUR Module by November of the year when the total number of reporters for each option reached 100. Hospitals' characteristics were self-reported to NHSN, except for hospital membership in a large healthcare system (≥100 hospitals), which was determined by reviewing online hospital composition information for large systems. Results: Each option accumulated ≥100 hospital adopters in the fifth year (AU, 2015) and fourth year (AR, 2017) of its availability. Compared with 5, 382 HAI-only reporters, 119 early AU adopters were typically larger (median number of beds: 152 vs. 80, P < 0.001), teaching hospitals (71% vs. 41%, P < 0.01) and had a leadership supported antimicrobial stewardship program (ASP) (98% vs. 86%, P < 0.001). Compared with 5375 HAI-only reporters, 126 early AR adopters were more likely to be larger (median number of beds: 201 vs. 80, P < 0.001), teaching hospitals (71% vs. 41%, P < 0.001) and produced an antibiogram at least annually (99% vs. 91%, P < 0.001). A significant proportion of AU (42%) and AR (57%) early adopters belong to a large healthcare system. Conclusion: The early hospital adopters in NHSN's AUR Module were typically larger teaching hospitals at which some ASP elements were in use, and many of these initial adopters were part of large healthcare systems. These findings suggest that internal organizational factors contribute substantially to hospitals' voluntary participation in AUR surveillance. Disclosures: All authors: No reported disclosures.